ОСНОВНІ ТЕНДЕНЦІЇ ТРАНСФОРМАЦІЇ СУЧАСНОЇ ПРОФЕСІЙНОЇ КУЛЬТУРИ - Fabryka А. (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
Introduction. Professional culture undergoes regular changes, as the nature of any profession requires constant improvement of its theoretical foundations and the modernization of approaches to performing professional tasks. However, the changes observed today are distinguished by their scale, depth, and rapid pace. They are primarily driven by globalization, the influence of Westernization (particularly Americanization) on the organizational context of professional activity, and the development of new technologies. These factors collectively define the main trends in the transformation of professional culture. The aim and tasks. The article aims to identify the main trends in the transformation of modern professional culture. Achieving this goal involves defining of the concept of professional culture and its main elements; assessing changes in professional culture resulting from globalization and the impact of Westernization on the organizational context; and analyzing the effects of technological development on the professional sphere of society. Research methods. Structural-functional and systematic approaches are the methodological basis of the research. Research results. The study reveals that transnational professional organizations and management regimes emerging from globalization contribute to the unification of professional culture. Changes in the organisational context of professional activity through the intensive promotion of the Western, American model of organisational culture contribute to the bureaucratisation and commercialisation of the culture of the profession. As a result, the impact of technological development is predicted to increase the importance of professional skills such as the use of artificial intelligence and working with big data, analytical thinking, creative thinking, etc. Discussion. The definition of professional culture and the assessment of changes taking place in it are related to a specific approach to understanding the profession. In this regard, some of our findings may not coincide with the point of view of other authors. Conclusions. Professional culture is losing its national peculiarities and is being unified according to the Western standard. This process is accompanied by greater bureaucratization, commercialization, and technologization.